Role of prebiotic dietary fiber in periodontal disease: A systematic review of animal studies - Tailor, Rohan; Medara, Nidhi; Chopra, Aditi; Swarnamali, Hasinthi; Eberhard, Joerg; Jayasinghe, Thilini N. (Frontiers in Nutrition, 2023)
Background: Periodontitis is a chronic inflammatory condition affecting the supporting structures of a tooth in the oral cavity. The relationship between dietary fibre and periodontitis is poorly understood. The objective of this systematic review is to investigate if an intake of dietary fibre modulates periodontal disease in animal models and any concomitant effects on systemic inflammation, microbiota and their metabolites. Methods: Animal studies using periodontitis models with any form of fibre intervention were included. Studies with comorbidities that were mutually inclusive with periodontitis and animals with physiological conditions were excluded. Search strategy with MeSH and free-text search terms were finalised and performed on the 22nd of September 2021.CINAHL Complete, EMBASE, MEDLINE, SciVerse Scopus® and Web of Science Core Collection databases were used to identify studies. SYRCLE’s risk of bias tool and CAMARADES were used for quality assessment. Results were synthesised utilising Covidence© web-based platform software to remove duplicates, and the remaining studies were manually filtered. Results: A total of 7141 articles were retrieved from all databases. Out of 24 full-text articles assessed for eligibility, four studies (n=4) were included. Four studies involved the use of β-(1,3/1,6)-glucan (n=3) and mannan oligosaccharide (n=1) at differing dosages for different study durations. All studies utilised a ligature-induced model of periodontitis in rats, either Wistar (n=3) or Sprague-Dawley (n=1). A dose-dependent relationship between the increased fibre intake and decrease in alveolar bone loss and pro-inflammatory markers was observed. Conclusion: The number of included studies is limited and narrow in scope. They highlight the importance of pre-clinical trials in this field with broader dietary fibre intervention groups before proceeding to clinical trials. The use of dietary fibre as an intervention shows promise in the reduction of inflammatory conditions like periodontitis. However, further research is required to delineate the relationship between diet and its effects on microbiota and their metabolites such as short chair fatty acids in animal models of periodontitis.